Broccoli cultivation with organic and inorganic sources of nitrogen and its effects on the nutrients balance (Bangladesh Journal of Agricultural Research, 2026)
The experiment was conducted on broccoli var. Premium Crop at Bangabandhu Sheikh Mujibur Rahman Agricultural University during the period from November, 2014 to March, 2015 with 24 treatment combinations (IPNS based) comprised with 4 inorganic sources of nitrogen as 140, 160 and 180 kg USG N ha-1 and 180 kg PU N ha-1 and 6 levels of  organic nitrogen sources as i) 1 ton mustard oil cake ha-1; ii) 2 ton mustard oil cake ha-1; iii) 2 ton poultry manure ha-1; iv) 3 ton poultry manure ha-1; v) 3 ton cow dung ha-1and vi) 5 ton cow dung ha-1 were considered. Results revealed that integration of organic and inorganic N sources have a little influence on soil physical and chemical properties of soil and its affects on soil nutrient balance. Post harvest soil organic carbon content was significantly influenced by the organic-inorganic N management approach, but no influence on soil pH, bulk density and partical density. However, a significant effect was found on post harvest soil nutrient balance where K showed a (-) ve balance but N with a little exception, P, S and B showed (+) ve balance which was affected by the organic-inorganic integrated N management approach. But better soil physical and chemical properties as well as higher (+) ve nutrient balance was found with higher rate of USG-organic manure as compared to that of PU-organic manure integration.Bangladesh J. Agril. Res. 48(1): 47-68, March 2023